Lands and peoples. The world in color. Volume 4 : southern and eastern Asia - Merrick, Helen Hynson
Afghanistan -- India -- Pakistan -- Kashmir -- Tibet, Nepal, Bhutan, Sikkim -- Burma -- Ceylon -- Malaysia and Singapore -- Thailand -- Cambodia, Laos, Vietnam -- Taiwan -- China -- Sinkiang -- Mongolia -- Peking -- Japan -- Tokyo -- Korea